CONIDIAL DISTRIBUTION OF FRESHWATER HYPHOMYCETES OF AN IRANIAN RIVER: ZAYANDE-ROUD (Journal of Sciences, Islamic Republic of Iran)
There is no published report regarding Iran's aquatic hyphomycetes. In an attempt to identify species of aquatic hyphomycetes in a river in central Iran (Zayande-Roud River), conidial frequency and distribution were determined by filtration. Water samples were collected monthly from two stations 55 km apart and filtered through millipore filters (5 um pore sizes). This was carried out for seven months starting in March 1990. Species identified are as follows: Alatospora acuminata, Anguillospora sp. 1; Clavariopsis aquatica, Lunulospora curvula, Tetracladium marchalianum,Tricladium sp. and Vargamyces aquaticus. Except for T. marchalianum, which was not present on filter papers after March, all other species were present at least till May with Anguillospora sp. 1 and V. aquaticus being recorded in August. Conidial frequency declined steadily from March through September. This might relate to declining organic resources available in the river.